Greenwashing The Global South: Carbon Markets and the ‎Legacy of Colonial Extraction: Greenwashing The Global South: Carbon Markets and the ‎Legacy of Colonial Extraction - Irawan, Angela Keisha Putri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This paper critically examines carbon offset markets through a postcolonialism lens, ‎arguing that these mechanisms embody a form of climate colonialism. Although often ‎presented as pragmatic solutions to global climate change, carbon offsets tend to reproduce ‎entrenched patterns of exploitation and inequality. Specifically, carbon offsets enable the ‎Global North to continue emitting greenhouse gases while outsourcing environmental ‎responsibility to the Global South, which effectively becomes a carbon sink. Drawing on ‎qualitative analysis on policy discourses, real-world case studies, and postcolonial theory, ‎this research examines how carbon markets facilitate land dispossession, resource ‎extraction, and the accumulation of ecological debt. These processes echo historical colonial ‎structures of domination and dependency. The paper foregrounds critical perspectives from ‎the Global South, highlighting resistance to carbon offset practices and emphasizing the ‎need for decolonial approaches to climate governance. Ultimately, it challenges dominant ‎‎“green economy” narratives and advocates for climate justice rooted in equity, historical ‎accountability, and non-market-based alternatives.‎